Perilaku asertif dengan harga diri mahasiswa dalam melaksanakan pembelajaran daring - Rizki Maulana Hidayatullah; Nur Alifah (PSYCOMEDIA : Jurnal Psikologi, 2022)
Self esteem is one factor that can inflate behavior assertive someone, with evaluation self describing how his precious and also understood he able to encourages individual competence for easy expressing himself into the area. This study was conducted in form to track the relationship between the price of behaviors assertive students during a pandemic. Used for the study sample was taken using all the people in every class with a total some 200 people. Analysis techniques the data used was pearson correlation. The result of the research is that there a positive relationship between the behaviors assertive students with the significance and value of 0.000 coefficient 0.673 obtained.